Optimization of Concentration and EM4 Augmentation for Improving Bio-Gas Productivity from Jatropha curcas Linn Capsule Husk - G.A, Praptiningsih; Hendroko, Roy; Wahono, Satriyo K; Sasmito, Andi; O. Nelwan, Leopold; Nindita, Anggi; Liwang, Tony (International Journal of Renewable Energy Development, 2014)
Most literature suggests that two-phase digestion is more efficient than single-phase. The series of two-phase digestion studies have been conducted from 2011 to 2013 at the research farm of PT Bumimas Ekapersada, West Java, Indonesia. This paper reports on a research on optimation of concentration and augmentation of EM-4 (effective microorganism-4), a local commercial decomposer, as efforts to stabilize a biogas technology which made from husk capsules of Jatropha curcas Linn (DH-JcL). The studies of increasing organic loading rate (OLR) for the two-phase digestion was conducted to improve efficiency.Â  The concentration variable studied was 1: 8 (1 part DH-JCL and 8 parts water), compared to 1: 12 as a control. The augmentation treatment is the addition of EM-4 by 5% (v/v). It was also examined the augmentation of F2-EM4 (150 times duplication of EM-4) due to cost consideration. The studies were conducted in the laboratory which using a liter and two liters of glass digester and glass wool as immobilized growth. The results of this study support the previous studies: the optimum concentration was 1: 8, EM-4 was able to increase biogas production in two-phase digestion, yet biogas production decrease at single-phase. F2-EM4â€™s ability to support production of biogas were equivalent to that of EM-4.